1991
DOI: 10.1007/bf00643737
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin releasing hormone and gonadotropin secretion in physically active males after acute exercise

Abstract: Plasma concentrations of corticotropin releasing hormone (CRH) and the serum concentrations of luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone, adrenocorticotropic hormone (ACTH) and cortisol were measured in seven physically active males after acute exercise on a treadmill using the Bruce protocol. Measurements were made in the basal pre-exercise state, immediately after exercise, and at 30-min intervals for 3 h after exercise. Serum LH concentrations declined following exercise rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…In part support of this notion, the heart rates of the gymnasts in the present study only transiently exceeded the aerobic training threshold of approximately 160 beats á min A1 cited for prepubertal children (Shephard 1992). Although anaerobic exercise has also been shown to be a potent stimulus for eliciting an increase in cortisol concentrations (Buono et al 1986;Elias et al 1991), it appears that the intermittent short-duration bouts of exercise associated with the present training regime were not of sucient intensity to elicit a large morning adrenocortical response in the male gymnasts, despite daily training sessions exceeding 3 h. The apparent lack of response may also be attributed to the fact that the diurnal variation in morning serum cortisol concentrations is much more pronounced than that in the afternoon (Hakkinen et al 1988), which may have masked any exercise-induced alterations that had occurred. In addition, it has been suggested that cortisol levels may actually decrease following low-intensity physical activity (less than 50% of maximal oxygen uptake), presumably due to increased removal from the circulation or decreased adrenocortical activity (Viru 1985).…”
Section: Discussionmentioning
confidence: 49%
“…In part support of this notion, the heart rates of the gymnasts in the present study only transiently exceeded the aerobic training threshold of approximately 160 beats á min A1 cited for prepubertal children (Shephard 1992). Although anaerobic exercise has also been shown to be a potent stimulus for eliciting an increase in cortisol concentrations (Buono et al 1986;Elias et al 1991), it appears that the intermittent short-duration bouts of exercise associated with the present training regime were not of sucient intensity to elicit a large morning adrenocortical response in the male gymnasts, despite daily training sessions exceeding 3 h. The apparent lack of response may also be attributed to the fact that the diurnal variation in morning serum cortisol concentrations is much more pronounced than that in the afternoon (Hakkinen et al 1988), which may have masked any exercise-induced alterations that had occurred. In addition, it has been suggested that cortisol levels may actually decrease following low-intensity physical activity (less than 50% of maximal oxygen uptake), presumably due to increased removal from the circulation or decreased adrenocortical activity (Viru 1985).…”
Section: Discussionmentioning
confidence: 49%
“…The cortisol responses seen during this study were surprising, considering that anaerobic exercise has generally been considered to be a potent stimulus for eliciting an increase in cortisol concentrations (Buono et al 1986;Elias et al 1991;Farrell et al 1983;Kindermann et al 1982). An elevation in cortisol concentration has generally been seen immediately following longer duration (more than 10 min), high intensity exercise (Elias et al 1991;Farrell et al 1983).…”
Section: Discussionmentioning
confidence: 85%
“…An elevation in cortisol concentration has generally been seen immediately following longer duration (more than 10 min), high intensity exercise (Elias et al 1991;Farrell et al 1983). During intense exercise of shorter duration (2 min), it has been found that cortisol concentrations do not appear to increase immediately postexercise but rather, may increase 15 min following exercise (Buono et al 1986;Kindermann et al 1982).…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly true of GH, PRL, and pro-opiomelanocortin-derived peptides such as ACTH, P-endorphin, and P-lipotropin (1- 7,9,11,19,20). Other hormones such as the gonadotropins, particularly LH.…”
Section: Discussionmentioning
confidence: 96%